2016
DOI: 10.1093/icvts/ivw209
|View full text |Cite
|
Sign up to set email alerts
|

The role of posterior aortopexy in the treatment of left mainstem bronchus compression

Abstract: The intrathoracic location of the left mainstem bronchus predisposes it to compression. Vascular anomalies represent the most frequent causes. Aortopexy has been advocated as a safe and useful method to relieve the compression, and our results confirmed these findings. Management of these patients is challenging and requires a multidisciplinary team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
0
28
0
2
Order By: Relevance
“…3 In their series of 18 patients, Arcieri et al reported associated malformations in 16 children, which included CHDs, oesophageal atresia, and trachea-oesophageal fistula. 4 Our patient had a structurally normal heart, but had associated pectus excavatum.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…3 In their series of 18 patients, Arcieri et al reported associated malformations in 16 children, which included CHDs, oesophageal atresia, and trachea-oesophageal fistula. 4 Our patient had a structurally normal heart, but had associated pectus excavatum.…”
Section: Discussionmentioning
confidence: 69%
“…Symptoms may sometimes persist after aortopexy, due to secondary bronchomalacia, and may require bronchial stenting for symptom relief. 4 Arcieri et al reported residual bronchomalacia in 44% of their cases. 4 Repeat bronchoscopy at one-year follow-up revealed normal caliber of bronchus with no residual malacia in our patient.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Others have tried posterior aortopexy—suturing the descending aorta to the thoracic vertebrae—to address left mainstem bronchomalacia. Unfortunately, in the largest study of this technique, eight out of 18 of children were found to have residual severe left mainstem bronchomalacia requiring a tracheostomy (n = 1) or placement of internal stents (n = 7) …”
Section: Discussionmentioning
confidence: 99%
“…study of this technique, eight out of 18 of children were found to have residual severe left mainstem bronchomalacia requiring a tracheostomy (n = 1) or placement of internal stents (n = 7). 23 Jennings has pioneered tracheobronchopexy, 6 in which the posterior (membranous) trachea is sutured to the anterior spinal ligament and/or the anterior (cartilaginous) trachea and/or bronchi are sutured to the sternum. In a recent case series, authors report no early or late deaths.…”
Section: Discussionmentioning
confidence: 99%